The Transition in East Germany: When Is a Ten‐Point Fall in the Gender Wage Gap Bad News? - Hunt, Jennifer (Journal of Labor Economics, 2002)
The gender wage gap in East Germany has narrowed by 10 percentage points in transition, but women have experienced much more severe employment difficulties than men. Using the German Socio‐Economic Panel for 1990–94, I show that on balance women have lost relative to men. Almost half the relative wage gain is due to exits from employment of the low skilled, who are disproportionately women. The female employment decline is not primarily voluntary: more than half the gender gap in the hazard rate from employment reflects a general fall in demand for low‐skilled workers. Reduced child care plays no role.